2024
DOI: 10.3390/ani14040561
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Gills Response to Cadmium Exposure in Greenfin Horse-Faced Filefish (Thamnaconus septentrionalis): Oxidative Stress, Immune Response, and Energy Metabolism

Xuanxuan Zhang,
Wenquan Zhang,
Linlin Zhao
et al.

Abstract: Cadmium (Cd) pollution has become a global issue due to industrial and agricultural developments. However, the molecular mechanism of Cd-induced detrimental effects and relevant signal transduction/metabolic networks are largely unknown in marine fishes. Here, greenfin horse-faced filefish (Thamnaconus septentrionalis) were exposed to 5.0 mg/L Cd up to 7 days. We applied both biochemical methods and multi-omics techniques to investigate how the gills respond to Cd exposure. Our findings revealed that Cd exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…However, the present study revealed that NOX (CL1542.Contig3_All) was significantly induced at both 3 and 48 h time points, whereas GST (CL355.Contig7_All) was suppressed. In addition, the transcription level of glutathione peroxidase (GPx) (CL5985.Contig3_All) was up-regulated at 3 h and downregulated at 48 h. Similar to our results, in Thamnaconus septentrionalis exposed to cadmium (Cd), the increase in antioxidant enzyme activity in the short term can effectively remove ROS, but long-term Cd exposure weakens the organism's antioxidant defense ability [72]. Therefore, we speculated that after Cu exposure, GPx has a stronger protective effect on M. rosenbergii compared to GST.…”
Section: Discussionsupporting
confidence: 84%
“…However, the present study revealed that NOX (CL1542.Contig3_All) was significantly induced at both 3 and 48 h time points, whereas GST (CL355.Contig7_All) was suppressed. In addition, the transcription level of glutathione peroxidase (GPx) (CL5985.Contig3_All) was up-regulated at 3 h and downregulated at 48 h. Similar to our results, in Thamnaconus septentrionalis exposed to cadmium (Cd), the increase in antioxidant enzyme activity in the short term can effectively remove ROS, but long-term Cd exposure weakens the organism's antioxidant defense ability [72]. Therefore, we speculated that after Cu exposure, GPx has a stronger protective effect on M. rosenbergii compared to GST.…”
Section: Discussionsupporting
confidence: 84%